Autotrophic and heterotrophic microalgae and cyanobacteria cultivation for food and feed: life cycle assessment. (December 2017) - Smetana, Sergiy; Sandmann, Michael; Rohn, Sascha; Pleissner, Daniel; Heinz, Volker
Highlights: LCA was performed for pilot industrial microalgae cultivation and processing. The study focused on autotrophic and heterotrophic cultivation of microalgae. Microalgae protein powders were more impacting than traditional concentrates. High-moisture extruded heterotrophic Chlorella was more beneficial than pork and beef. Chlorella cultivation on food waste resulted in more sustainable protein source. Abstract: The lack of protein sources in Europe could be reduced with onsite production of microalgae with autotrophic and heterotrophic systems, owing the confirmation of economic and environmental benefits. This study aimed at the life cycle assessment (LCA) of microalgae and cyanobacteria cultivation ( Chlorella vulgaris and Arthrospira platensis ) in autotrophic and heterotrophic conditions on a pilot industrial scale (in model conditions of Berlin, Germany) with further biomass processing for food and feed products. The comparison of analysis results with traditional benchmarks (protein concentrates) indicated higher environmental impact of microalgae protein powders. However high-moisture extrusion of heterotrophic cultivated C. vulgaris resulted in more environmentally sustainable product than pork and beef. Further optimization of production with Chlorella pyrenoidosa on hydrolyzed food waste could reduce environmental impact in 4.5 times and create one of the most sustainable sources of proteins.